COVID-19 stay-at-home order in Tyrol, Austria: sports and exercise behaviour in change?. (August 2020) - Schnitzer, M.; Schöttl, S.E.; Kopp, M.; Barth, M.
Abstract: Objectives: The aim of the study was to investigate differences in the frequency and types of engagement in sports before, during and after the coronavirus disease 2019 (COVID-19) stay-at-home order in Tyrol, Austria. Study design: A representative population survey was conducted. Methods: A sample of Tyroleans (N = 511) was questioned by a market research institute via an online questionnaire or telephone survey. Results: During the stay-at-home order, participants engaged less in sports than before and after the restrictions. However, within-group analyses revealed increasing sport participation in less active groups when comparing the pre- and post-COVID-19 period. Conclusions: Despite the restrictions during the stay-at-home order, respondents did engage in sports and promoted their health. Nevertheless, it is still necessary to investigate the long-term effects of the COVID-19 crisis on sports and exercise behaviour as well as the extent to which sports policy measures may be able increase sports participation. Highlights: In general, participants engaged less in sports during the coronavirus disease 2019 (COVID-19) stay-at-home order. Within-group analyses showed increased sports participation in less active groups. Respondents adhered to the outdoor sports ban and did home training instead. Appropriateness of regulations implemented in the context of the COVID-19 pandemic was measured. Crises such as COVID-19 might have a long-term impact on sports participation.